The Effect of Breathing Techniques on Enhancing the Effect of Massage in Reducing the Pain in the Second Stage of Labour: A Parallel Randomized Clinical Trial - Haseli 1, Arezoo; Chenari 2, Zahra; Nami 2, Mona; Jahdi 3, Fereshteh; Neisani Samani 4, Leila; Haghani 5, Hamid (Shahroud Journal of Medical Sciences, 2019)
Background: massage is commonly used for labor pain relief and has been the subject of research for many years. The present study was conducted to evaluate the effect of abdominal massage on labor pain as well as assessing the effect of breathing techniques in reducing the labor pain by massage.Methods: In this parallel-randomized clinical trial, 96 nulliparous women from were recruited from July to December 2010 and allocated into two experimental groups (massage only and massage with breathing groups) and one control group. Before allocation, an informed consent form was obtained from all the subjects. Visual Analog Scale (VAS) was used to assess the pain during active and transitional phases of labor 30and 60 min after intervention. The duration of active phase, path of delivery, episiotomy, neonatal Apgar score at 1 and 5 min and neonatal birth weight were considered as secondary outcomes of this study.Results: After 30 and 60 min of intervention in active phase, the mean VAS scores of both experimental groups significantly decreased compared to the control group (P<0.01). No significant difference was observed in mean VAS scores after intervention on transitional phase (P>0.05). In second stage of labor, the mean VAS scores of massage with breathing group were significantly lower than the massage and control groups (P<0.05). Both experimental groups had significant shorter time used in active phase of labor than the control group (P<0.05).Conclusions: Breathing techniques only strengthen the pain-relieving effect by the massage in the second stage of labor. Therefore, it is recommended to use breathing techniques, especially in the second stage of labor.